THE TRAVEL TIME PERFOMANCE ANALYSIS OF THE COMMUTER LINE TRAIN (KRL) (CASE STUDY: THE COMMUTER LINE TRAIN BLUE LINE CORRIDOR, BEKASI - JAKARTA KOTA) - Bayu Aji Pangestu; Irnanda Satya Soerjatmodjo; Noviandi Putra Darsono (University Of Muhammadiyah Jakarta, 2022)
On the commuter line trains (the KRL), the Bekasi-Jakarta City Blue Line corridor has a buildup of passengers so that it can reduce travel time. Based on the regulation of the Minister of Transportation No. 63 of 2019 on Minimum Service Standards for Transportation of People by Train, the maximum delay tolerance for urban trains is 15 minutes from the total scheduled travel time. The method used is the depiction of working charts and calculations of statistical analysis with standard deviation in SPSS application version 26. The difference in the comparison of scheduled travel times with those in the field is determined by using Microsoft Excel for Windows version 2015. The performance of Blue Line routes (the KRL) was reviewed based on travel time using the SPSS (Statistical Package for the Social Sciences) analysis tool version 26. The standard deviation results using the SPSS KA 1341 analysis tool have a higher deviation standard result of 10.82, which means that the train has a higher travel time delay than the train of PT Kereta Commuter Indonesia (KCI), which experienced an average delay of 4 minutes. The cause of the delay consists of several factors, including the queue of passengers who want to get into the train and the fact that traffic on the blue line KRL route is congested. Because it has to alternate with intercity trains, and the KRL must wait.